The Maori Student Nurse Experience of Cohorting: Enhancing Retention and Professional Identity as a Maori Nurse. - Zambas, Shelaine I.; Dewar, Jan; Tokomauri McGregor, Jenny (Nursing Praxis in Aotearoa New Zealand, 2023)
Despite decades of work by tertiary providers to increase the Māori nursing workforce, there has been little change in the numbers of Māori nurses graduating from schools of nursing. The call for more culturally responsive teaching and learning strategies saw one tertiary provider implement Māori student cohorts for labs and tutorials in year one and two of the Bachelor of Health Science Nursing programme. This research explored the student experience of the cohorts using a hermeneutic methodology within a Māori-centred approach. Students in year two and three of the programme who had participated in the cohorts were invited to join focus groups to share their experiences. Data from the focus groups was analysed using van Manen's approach with a Māori lens. The themes of whanaungatanga (connection), tikanga (correct practice), wānanga (learning conversation) and manaakitanga (ethic of care) emerged from the data. Cohorting was identified as a culturally responsive teaching and learning strategy. It provided a safe space for learning in what is a predominantly western monocultural system. It was not suffient on its own however. Cohorting of Māori students needs to be supported by teaching practices which include tikanga Māori, wānanga as a formal teaching strategy and the overt demonstration of manaakitanga to ensure it meets the needs of Māori nursing students. When integrated into programmes of study, Māori student cohorts have the potential to not only support retention, but also the development of the student's professional identity as a 'Māori' nurse.